'It's my diabetes': Co-production in practice with young people in delivering a 'perfect' care pathway for diabetes. (1st July 2018) - Sharpe, Darren; Green, Emma; Harden, Angela; Freer, Rachelle; Moodambail, Abdul; Towndrow, Steven
Abstract : This paper considers how young people can help commissioners and providers better understand and address the options and barriers of delivering a perfect care pathway. This applied health study was funded by the National Institute of Health Research (NIHR) in England and a local clinical commissioning group (CCG) responsible for the organization and delivery of NHS services in a socially deprived, ethnically diverse urban locality. The research team was mixed – in terms of age, ethnicity, faith-identities and backgrounds – and worked together over one year to co-produce commissioning guidance. Guidance is intended for use by clinical commissioning groups to support them in commissioning health diabetes services. Our goal was to work with young people to help us understand the options and barriers they face when given a diagnosis of diabetes, and using NHS services. While our NHS partners can provide the latest medical and academic input into managing diabetes, young people have first-hand experience of managing diabetes, the highs and the lows, and only they can provide the inspiration for what would make the service better, now and in the future. With this focus in mind, young people joined the research team to help shape and implement new commissioning guidance. This paper offers the opportunity to reflect on the strengths and weaknesses in involving young people in health service design.